Pengaruh Potongan Harga, Bonus Kemasan, Tampilan dalam Toko terhadap Keputusan Pembelian Impulsif. - Allen Kristiawan; Ika Gunawan; Vinsensius Vinsensius (Forum Manajemen Indonesia (FMI), 2018)
The competition among retail owners cannot be avoided, with various promotions offered, retailers are competing to win the hearts of consumers. The more new companies appear, the more offered products on the market. Of course this situation makes it easier for producers to market their products and for retailers themselves they will always compete to do more creative things in an effort to attract potential consumers. Price discounts and bonus packs are the most widely used sales promotions, both online and offline sales (Chen, Marmorstein, Tsiro, & Rao, 2012; Dawson & Kim 2009). In-store Display (display in store) is the layout of goods by taking into account the elements of grouping of types and uses of goods, neatness and beauty so that it seems attractive and directs consumers to see, encourage, and decide to buy (Ngadiman 2008: 329). The population of this research is consumers of hypermarkets and supermarkets in the city of Bandung. The sample in this study are consumers who shop at Carrefour hypermarkets and Yogya supermarkets. The statistical method used in this study is multiple regression. Based on the results of the statistics carried out, the results obtained for Carrefour hypermarkets for bonus packaging have no effect and in Yogya supermarkets the price discount has no effect on impulsive purchases. Keywords: Discounted prices, Bonus packaging, In-store display, Impulsive purchases.